Ultrasonographic evaluation of early knee osteoarthritis - Kumahashi, Nobuyuki; Kuwata, Suguru; Takuwa, Hiroshi; Uchio, Yuji (Annals of Joint, 2018)
Ultrasonography (US) is non-invasive, fast, easy-to-use and safe. The quality and resolution of US has been improved in recent years. Recently, in orthopaedics, US measurements have been used for the diagnosis of osteoarthritis (OA), which can provide the basis for proper early treatment. In this chapter, we review the published articles about US evaluation of knee OA, especially focused on cartilage, including probe selection, probe direction, evaluation site, knee position, measurement of thickness, echogenesis and superficial sharpness of cartilage with histological findings and accuracy to detect early OA changes.